Market Penetration As A Proposed Marketing Strategy: Case Of PT. Atourin Teknologi Nusantara - Nisa Aulia Nur Setiawan; Harimukti Wandebori (UNIVED Press, 2025)
Indonesia’s tourism industry has great potential for economic growth, driven by its natural and cultural richness and the increasing adoption of digital platforms, which are increasingly being introduced. As one of the players in the industry, PT Atourin Teknologi Nusantara (Atourin) faces challenges in increasing brand awareness and attracting travelers to use their services, which offer a variety of local attractions. This study aims to identify Atourin’s target market, explore the factors influencing brand awareness and purchase intention, and propose effective marketing strategies to increase Atourin’s presence. A mixed methodology with qualitative and quantitative approaches was conducted, combining interviews and questionnaire distribution. Data analysis used clustering to group the identified market segment, then findings of external and internal analysis using SWOT, TOWS matrix, and Ansoff matrix. Based on the findings, it is known that Atourin, as a technology-based startup in the tourism industry, certainly has strengths in the field of tourism technology and knowledge. Unfortunately, the level of awareness of the Atourin brand in the local tourist market is still low. This study recommends market penetration that focus on increasing market share with existing products in existing markets through the use of social media, increasing customer retention through loyalty programs, and strategic collaborations to strengthen Atourin’s market position and drive business growth in Indonesia’s digital tourism industry.